Efficient electrocatalytic hydrogenation of guaiacol via construction of electron-rich platinum active centers through alloying - Wang, Peng; Dai, Qiqi; Zhang, Danlu; Liu, Chuanfu; Lan, Wu (Journal of colloid and interface science, 2025)
[Display omitted] •A robust PtRuCo alloy was prepared by a facile electrodeposition method.•Efficiently electrocatalytic hydrogenation of guaiacol was achieved.•Ru and Co alloying enriches the Pt and improve the hydrodeoxygenation reactivity. The electrocatalytic conversion of lignin model compounds into high-value chemicals represents a sustainable and environmentally friendly approach. In this study, a PtRuCo alloy catalyst was synthesized through a simple, cost-effective electrodeposition method. This catalyst demonstrated exceptional performance in the mild and efficient electrocatalytic hydrogenation (ECH) of guaiacol, achieving an impressive 84.6 % yield and showing significant potential for hydrogenating other related monomers. The PtRuCo exhibited remarkable stability and superior electrochemical performance under acidic conditions. The electron distribution within the alloy was thoroughly investigated using X-ray photoelectron spectroscopy (XPS) and theoretical calculations. These analyses provided valuable insights into its outstanding ECH properties. Moreover, in-situ Fourier Transform Infrared Spectroscopy (FTIR) was employed to monitor the evolution of reaction intermediates, establishing a robust experimental foundation for elucidating the reaction pathway. This study offers theoretical guidance for designing tailored catalysts for specific target reactions through detailed electronic structure analysis.